Coincidental values of responding to climate in contemporary Chinese architectural design - Biying Zuo; Keisuke Kitagawa; Ye Chen (Journal of Asian Architecture and Building Engineering, 2025)
Relying solely on equipment and uncritical adoptions of technological strategies to control climate conditions can result in problems of the detachment of climate from the architectural design process, monotonous forms and lack of regional characteristics. To address these problems that may arise in contemporary China, research on the coincidental values generated with the climate-responsive operations including expressions of aesthetics, culture, emotions, regional characteristic is of great significance. The paper examines coincidental values of responding to climate by analyzing architects’ text descriptions of 263 design works from the year 2000 to 2021. The results provide a framework of 27 types of coincidental values as references for climate-responsive architectural designs. Mechanisms of creating coincidental values and subtle regional characteristics are revealed through analyses of these 27 types. Based on these findings, the paper proposes suggestions for contemporary Chinese climate-responsive designs, calling for more various cultural expressions beyond traditional or vernacular cultures, more interactions with positive aspects of climate, and broader range of the compromise between human behaviors and climate conditions.